C++ Recipes: A Problem-Solution Approach - Sutherland, Bruce (Springer, 2015)
C++ Recipes: A Problem-Solution Approach is a handy code cookbook reference guide that cover the latest C++ 14 as well as some of the code templates available in the latest Standard Template Library (STL).